Strategies For Implementing Offline Learning After The Covid-19 Pandemic - Mastur Mastur (Edumaspul: Jurnal Pendidikan, 2022)
This study aims to discover what learning strategies educators can still apply when face-to-face learning has resumed. With this strategy, learning can still take place well and efficiently. The research method used is Descriptive-Quantitative. Sampling technique using purposive sampling. The informants, in this case, were students of MTs Aswaja Tunggangri Kalidawir Tulungagung with specific criteria, which were determined to be 58 respondents. Data collection techniques using questionnaires (Questionnaire). This instrument was created with ten questions using Google Forms and then distributed via Whatsapp. The results of this study indicate that face-to-face learning strategies (Offline learning) that can be carried out after the Covid-19 pandemic are 1). Teachers constantly innovate in the learning process 2). Maintain and use learning applications that can be given to children 3). Teachers must have skills and facilitators in learning activities 4). Maintain intensive communication between parents, children and educators.